2012
DOI: 10.3390/membranes2040783
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Analysis of Current and Mechanical Properties of Nafion® Studied by Atomic Force Microscopy

Abstract: The conductivity of fuel cell membranes as well as their mechanical properties at the nanometer scale were characterized using advanced tapping mode atomic force microscopy (AFM) techniques. AFM produces high-resolution images under continuous current flow of the conductive structure at the membrane surface and provides some insight into the bulk conducting network in Nafion membranes. The correlation of conductivity with other mechanical properties, such as adhesion force, deformation and stiffness, were simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
71
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 35 publications
1
71
0
Order By: Relevance
“…In support of this assertion, we note the current-sensing atomic force microscopy (AFM) studies of Heisgen et al in which it is suggested that pores at the membrane's surface open, leading to better connectivity to the internal network of hydrophilic channels as a result of electrogenerated water being formed. 31 More specifically, when a bias potential is applied to the AFM electrode/membrane interface causing ORR, internal membrane pressures develop which is released by the opening of hydrophilic water channels at the surface, resulting in increased current flow. A similar effect is also postulated by Kreuer in conclusion of dynamic mechanical analyses (DMA) of membranes exposed to varying relative humidity, i.e., internal pressures in PFSA membranes resulting from increasing hydration levels are relieved by a reorganization of the morphology of the outer skin.…”
Section: Resultsmentioning
confidence: 99%
“…In support of this assertion, we note the current-sensing atomic force microscopy (AFM) studies of Heisgen et al in which it is suggested that pores at the membrane's surface open, leading to better connectivity to the internal network of hydrophilic channels as a result of electrogenerated water being formed. 31 More specifically, when a bias potential is applied to the AFM electrode/membrane interface causing ORR, internal membrane pressures develop which is released by the opening of hydrophilic water channels at the surface, resulting in increased current flow. A similar effect is also postulated by Kreuer in conclusion of dynamic mechanical analyses (DMA) of membranes exposed to varying relative humidity, i.e., internal pressures in PFSA membranes resulting from increasing hydration levels are relieved by a reorganization of the morphology of the outer skin.…”
Section: Resultsmentioning
confidence: 99%
“…The fraction of non-conductive/conductive area was retrieved from area analysis of the images. More details on the AFM measurements can be found in Hiesgen et al 12,17,18,71 For AFM analysis of MEAs, freshly prepared cross-sections were imaged. The cross-sections were cut by microtome after embedding the MEA into 2-component polyurethane (Teromix, BASF) for stabilization.…”
Section: Methodsmentioning
confidence: 99%
“…With PeakForce QNM-mode, mapping of local height, adhesion, stiffness (DMT modulus, stiffness proposed by Derjagin, Muller, Toropov in 1975), deformation, and dissipation was performed. 12,17,18 Atomic force microscopy takes advantage of the higher contrast in adhesion (pulloff) force and stiffness between the ionomer and the carbon/platinum components. 13 The local ionic current at constant relative humidity in a gastight chamber was recorded using a platinum coated catalytically active tip.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A skin layer thickness of 5 nm could be measured for Nafion NR212. 22,23 Upon contact with water, the ionic side groups can change their orientation within seconds, and the surface becomes hydrophilic. 18 At the interface with water, the structures tend to orient vertically to expose ionically conductive channels from the bulk to the exterior that supply an exit for water/proton exchange.…”
mentioning
confidence: 99%